2004
DOI: 10.1002/app.13432
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium carbonate and its purity on crystallization and melting behavior, mechanical properties, and processability of syndiotactic polypropylene

Abstract: Calcium carbonate-filled syndiotactic poly-(propylene) (CaCO 3 -filled s-PP) was prepared in a self-wiping, co-rotating twin-screw extruder. The effects of CaCO 3 of varying particle size (1.9, 2.8 and 10.5 m), content (0 -40 wt %), and type of surface modification (uncoated, stearic acidcoated, and paraffin-coated) on the crystallization and melting behavior, mechanical properties, and processability of CaCO 3 -filled s-PP were investigated. Non-isothermal crystallization studies indicate that CaCO 3 acts as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 29 publications
10
68
0
Order By: Relevance
“…It is well known that the commonly used reinforcing fillers for PP can also act as strong nucleating agents depending on the processing conditions used, degree of filler dispersion in the composite and filler surface coverage, thus, affecting the degree of crystallinity, rate of crystallization, crystal size and lamellae orientation and hence the composite properties [39][40][41][42]. Calorimetric studies reported on the composites investigated in the present study showed that under the processing conditions used in the study, the OMMT particles did not significantly affect the crystallinity of the polymer in the composites [21].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the commonly used reinforcing fillers for PP can also act as strong nucleating agents depending on the processing conditions used, degree of filler dispersion in the composite and filler surface coverage, thus, affecting the degree of crystallinity, rate of crystallization, crystal size and lamellae orientation and hence the composite properties [39][40][41][42]. Calorimetric studies reported on the composites investigated in the present study showed that under the processing conditions used in the study, the OMMT particles did not significantly affect the crystallinity of the polymer in the composites [21].…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, 15 the presence of dolomite or CaMg(CO 3 ) 2 was postulated to be the reason for the observed increase in the nucleation ability of 10.5 m CaCO 3 particles. Figure 10 illustrates the variation of the t 0.5 on the choice of the T f for neat s-PP#8 and s-PP#8 filled with 40 wt % 1.9 m CaCO 3 particles of different surface modificiations (uncoated, stearic acid-coated, and paraffin-coated).…”
Section: Effect Of Melt-annealing Temperaturementioning
confidence: 60%
“…26 Interestingly, despite the different nature of the s-PP resin investigated here in comparison with other s-PP resins investigated in a previous report, similar results were obtained in that the critical T f that was needed for these s-PP resins to attain the complete molten state after 5 min of melt-annealing period (t h ) was essentially identical (160°C). 26 Moreover, the t 0.5 values for s-PP#8 filled with both 20 and 40 wt % 1.9 m uncoated CaCO 3 particles did not vary much with the T f , possibly a result of the enhanced nucleation rates attributable to the presence of the CaCO 3 particles 15 and that the t 0.5 values for s-PP#8 filled with 20 wt % CaCO 3 particles were systematically greater than those for s-PP#8 filled with 40 wt % CaCO 3 particles, suggested that an increase in the filler content enhanced the crystallization rates of the resulting compounds. Figure 9 shows dependence of the t 0.5 on the choice of the T f for neat s-PP#8 and s-PP#8 filled with 40 wt % CaCO 3 particles of varying size (1.9, 2.8, or 10.5 m).…”
Section: Isothermal Crystallization Behavior Of Neat Spp#8 and S-pp#8mentioning
confidence: 94%
See 2 more Smart Citations